WHY TESTING IS IMPORTANT IN THE E-COMMERCE APPLICATION? - Lazda, Gintars; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The author performed an analysis why testing is important for e-commerce application. The work contains basic information about testing, software development and e-commerce.